Sejarah Pemerintahan Imeum Mukim di Aceh - Mahdi Syahbandir (Kanun Jurnal Ilmu Hukum, 2014)
Historically, the governance of Imeum Mukim is a legacy of the Aceh Empire. It is not created by the colonialism of the Dutch or the Indonesiian Government, but, it is created by the empire. The existency is a part of customary and conducted based on customs and customary law. This research explores such existence from the era of the Aceh Empire to nowadays. After the independence of Indonesia, its existence is influenced by the laws regulating Local and Villaage Governances. Surprisingly, the existence was not recognized by the Act Number 5, 1979. The Act Number 11, 2006 regarding Aceh Governance, it is admitted as one of the governance units under the head of subdistrict official and regulated by its own local laws. The History of Imuem Mukim Governance in Aceh